2007
DOI: 10.4049/jimmunol.178.5.2803
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus aureus Protein A Triggers T Cell-Independent B Cell Proliferation by Sensitizing B Cells for TLR2 Ligands

Abstract: B cells possess functional characteristics of innate immune cells, as they can present Ag to T cells and can be stimulated with microbial molecules such as TLR ligands. Because crude preparations of Staphylococcus aureus are frequently used as polyclonal B cell activators and contain potent TLR2 activity, the scope of this study was to analyze the impact of S. aureus-derived TLR2-active substances on human B cell activation. Peripheral B cells stimulated with chemically modified S. aureus cell wall preparation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
83
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(89 citation statements)
references
References 84 publications
6
83
0
Order By: Relevance
“…However, MID stimulation alone is not enough to drive B cells into IgM secretion (37,52). Data from Bekeredjian-Ding et al (53) have suggested a synergy in B cell activation between the Staphylococcus aureus B cell superantigen protein A (SpA) and TLR2 signaling. However, SpA and TLR2 signaling is not sufficient to induce IgM production, as seen with SpA-expressing bacteria (45) or rSpA with either ligands directed against TLR7 or TLR9.…”
Section: Discussionmentioning
confidence: 99%
“…However, MID stimulation alone is not enough to drive B cells into IgM secretion (37,52). Data from Bekeredjian-Ding et al (53) have suggested a synergy in B cell activation between the Staphylococcus aureus B cell superantigen protein A (SpA) and TLR2 signaling. However, SpA and TLR2 signaling is not sufficient to induce IgM production, as seen with SpA-expressing bacteria (45) or rSpA with either ligands directed against TLR7 or TLR9.…”
Section: Discussionmentioning
confidence: 99%
“…One characteristic of this Gram-positive bacterium is its very potent TLR2 activity that is mediated by membrane-anchored LP and can be easily detected in TLR2-transfected HEK293 cells (data not shown and Ref. 46). TLR2-active LP have, in fact, been proposed to represent its major immune stimulatory component (46 -48).…”
Section: Pdc Activation By Staphylococci Is Independent Of Tlr2-activmentioning
confidence: 99%
“…To do so, we chose different approaches. First, we compared two well-described S. aureus reference strains: Cowan I (SAC), a high producer of SpA, and Wood 46, a strain deficient in SpA protein expression due to a sigB deficiency (46,49,50). Both strains were comparable in regards to their IFN-␣ triggering potential ( Fig.…”
Section: S Aureus-induced Ifn-␣ Secretion Is Not Dependent On Proteimentioning
confidence: 99%
“…1). Ag encounter as simulated through BCR cross-linking has been reported to increase the sensitivity of B cell responses to several microbial ligands (36,48,49). To investigate the impact of BCR cross-linking on responses elicited by these TLR ligands, B cell proliferation was measured in the presence or absence of total anti-Ig.…”
Section: Characterization Of B Cell Responses Following Stimulation Wmentioning
confidence: 99%